FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA TERHADAP PENGGUNAAN DIGITAL PAYMENT DENGAN PENDEKATAN TAM DI UNIVERSITAS BALI INTERNASIONAL - Rettobjaa, Vitalia Fina Carla; Widnyani, Ni Made; Aristayudha, A.A. Ngurah Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p05, 2022)
The era of revolution 4.0 is the initial milestone of the birth of globalization in the world economy. The current movement of business progress is accompanied by developments in the field of information and communication technology. Technological developments in the economic sector are supported by financial technology. Financial transactions carried out by the Indonesian people are more than 50% using a payment system in the form of an e-wallet. One of them is digital payment, the OVO brand is a digital wallet service or electronic money in the form of a digital application that functions as a means of payment or online transactions developed by PT. International Visionet. The variety of digital payment applications offered makes students as consumers more selective in choosing applications that provide satisfaction for themselves. Therefore, it is important to know the factors that influence student satisfaction with the use of digital payments. The purpose of this study was to analyze the factors that influence student satisfaction with the use of digital payments (OVO) with the Technology Acceptance Model approach at the International Bali University. The research method used is quantitative with linear regression test.